Peningkatan Kompetensi Peternak dan Keberlanjutan Usaha Sapi Potong di Desa Oebkim Kecamatan Bikomi Selatan Kabupaten Timor Tengah Utara - Ture Simamora (Fakultas Pertanian, Universitas Timor, 2020)
Competence is the result of an empowerment process. Empowerment is a process that aims to provide power to the community or activities that make the community able to build themselves, able to work together. The purpose of this study was to analyze the characteristics of breeders, counseling support, external environmental support, competency level, level of sustainability and analyze the factors that influence the competence and sustainability of beef cattle business in Oebkim Village, Bikomi Selatan District, Timor Tengah Utara Regency. The results showed that the factors influencing the competence of farmers in Oebkim Village were external environmental support. Farmers' competence is reflected by their ability in marketing. Market and capital institutions have not yet fully functioned in beef cattle business. Some farmers still have difficulty in accessing capital and business credit so that farmers are limited in increasing the scale of their business. The factor influencing the sustainability of the beef cattle business in Oebkim Village is the characteristics of the breeders. Characteristics of farmers are reflected by age and education. Competence does not affect the sustainability of the beef cattle business in Oebkim Village.